58.5k views
1 vote
What is the solution to the system of equations?
y= 2/3x+3
x = –2

User Wyu
by
5.8k points

1 Answer

5 votes

Answer:


x = -2 and
y = (5)/(3)

Explanation:

Given


y = (2)/(3)x + 3


x = -2

Required

Determine the solution to the equations

From the second equation, we have the value of x already;

The next step is to substitute -2 for x in the first equation


y = (2)/(3)x + 3 becomes


y = (2)/(3)(-2) + 3


y = (-4)/(3) + 3


y = -(4)/(3) + 3

Take LCM


y = (-4 + 9)/(3)


y = (5)/(3)

Hence,


x = -2 and
y = (5)/(3)

User Raju Ahammad
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.